Usage of Gamification and Mobile Application to Reduce Food Loss and Waste: A Case Study of Indonesia - Kisusyenni Venessa; Heru Wijayanto Aripradono (Universitas Bina Darma, 2023)
Food loss and waste (FLW) are major global issues, and Indonesia has been identified as the world's second-largest contributor to this problem. Bappenas research indicates that FLW in Indonesia, particularly food waste, is increasing annually, with the household sector being the primary source. In response, we developed a gamification mobile application for FLW, drawing on a case study from Cechetti et al. to encourage households to reduce food waste. We tested the application's acceptance using the modified TAM model and analyzed the data using content analysis. Our findings provide insights into the potential of gamification to address FLW in Indonesia and contribute to environmental sustainability.